Late seroma complication in a breast augmentation patient with fibrin accumulation: a case report - Heewoong Yang; Jun Ho Park (Archives of Aesthetic Plastic Surgery)
Breast implant surgery is one of the most commonly performed aesthetic surgery around the world. Late seroma is a well known complication that is linked to breast implant-associated anaplastic large cell lymphoma (BIA-ALCL). However, there are some clinically confounding cases of late seroma that present with BIA-ALCL like symptoms. Here we report a case of a 30-year-old female patient who underwent bilateral breast augmentation that presented with a late seroma case with symptoms matching that of BIA-ALCL–abrupt swelling and pain–that was later diagnosed as abnormal accumulation of fibrin.